A rabbit model of cerebral microembolic signals for translational research: preclinical validation for aspirin and clopidogrel. (20th July 2016) - Zhou, X.; Kurowski, S.; Wu, W.; Desai, K.; Chu, L.; Gutstein, D. E.; Seiffert, D.; Wang, X.
Abstract : Essentials Microembolic signal (MES) is an independent predictor of stroke risk in patients. A rabbit model of cerebral microembolic signals was established. Therapeutic efficacy was demonstrated for aspirin and clopidogrel on microembolic signals. Potential translational value of this preclinical model of MES was demonstrated. Summary: Objectives: Cerebral microembolic signals (MESs) detected by transcranial Doppler (TCD) ultrasound constitute an independent predictor of stroke risk and prognosis. The aim of this study was to develop a novel preclinical model of MESs to facilitate translational research. Methods: A clinical TCD ultrasound machine was used to detect MESs in the cerebral circulation of New Zealand White rabbits. Technical feasibility was assessed for the measurement of MESs in the middle cerebral artery (MCA) by TCD. FeCl3 ‐induced carotid arterial thrombosis was optimized for the generation of endogenous microemboli. Ascending doses of two antithrombotic agents (aspirin and clopidogrel) were evaluated individually and in combination for their effects on both arterial thrombosis and MESs in a 30% FeCl3 ‐induced carotid arterial thrombosis model, along with ex vivo functional assays. Results: Dose‐dependent FeCl3 ‐induced arterial thrombosis studies showed that 30% FeCl3 resulted in the most consistent and reproducible MESs in the MCA (3.3 ± 0.7 MESs h −1 ). Ascending‐dose studies showed that the effective doses for 50% inhibition (ED50 ) of thrombus formation, based on integrated blood flow and thrombus weight, respectively, were 3.1 mg kg −1 and 4.2 mg kg −1 orally for aspirin, and 0.3 mg kg −1 and 0.28 mg kg −1 orally for clopidogrel. The ED50 values for MES incidence were 12.7 mg kg −1 orally for aspirin, and 0.25 mg kg −1 orally for clopidogrel. Dual treatment with aspirin (5 mg kg −1 ) and clopidogel (0.3 mg kg −1 ) resulted in significant reductions in cerebral MESs ( P < 0.05) as compared with monotherapy with either agent. Conclusions: Our study demonstrated the successful establishment of the MES model in rabbits, and it may provide translational value for MESs and ischemic stroke research.